Case Report: Eosinophilic Myenteric Ganglionitis in a Child With Hirschsprung's Disease: A Challenge in Pseudo-Obstruction - D'Auria, Enza; Calcaterra, Valeria; Maestri, Luciano; Meroni, Milena; Selvaggio, Giorgio Giuseppe Orlando; Villanacci, Vincenzo; Nebuloni, Manuela; Pelizzo, Gloria (Frontiers in Pediatrics, 2021)
Introduction: The presentation of eosinophilic myenteric ganglionitis (EMG) can be similar to that of Hirschsprung’s disease (HD). In a limited number of cases of pediatric patients, the diagnosis of both EMG and HD are reported. A case of pseudo-obstruction in EMG occurring in a child with HD diagnosis is discussed along with a literature review. Case presentation: A boy aged 2 years and 6 months presented with intractable constipation and abdominal distension. Histological HD diagnosis was carried out and transanal Soave pullthrough was performed. At the age of 3 years and 2 months, an infectious enterocolitis occurred. One month later, he presented with constipation, marked abdominal distension and melena. Full thickness colonic biopsies revealed eosinophilic myenteric ganglionitis. Specific IgE tests came back positive for several foods. Dietary exclusion was adopted with resolution of clinical symptoms and histologic remission. Conclusion: EMD may occur in patients with HD. At the onset, EMD may be associated with functional intestinal obstruction. The use of an elimination diet proved effective for the relief of symptoms. Long term follow-up is mandatory to define the timing of the reintroduction of foods.